Reasoning Otherwise: Leftists and the People's Enlightenment in Canada, 1890-1920 - McKay, Ian (Between the Lines, 2008)
In Reasoning Otherwise, author Ian McKay returns to the concepts and methods of 'reconnaissance' first outlined in Rebels, Reds, Radicals to examine the people and events that led to the rise of the left in Canada from 1890 to 1920. Reasoning Otherwise highlights how a new way of looking at the world based on theories of evolution transformed struggles around class, religion, gender, and race, and culminates in a new interpretation of the Winnipeg General Strike of 1919. As McKay demonstrated in Rebels, Reds, Radicals, the Canadian left is alive and flourishing, and has shaped the Canadian experience in subtle and powerful ways. Reasoning Otherwise continues this tradition of offering important new insight into the deep roots of leftism in Canada. --Publisher's description
Keywords: History; Politics and government; Right and left (Political science); Socialism

For a New Kind of History: A Reconnaissance of 100 Years of Canadian Socialism - McKay, Ian (Labour / Le Travail, 2000)
The turn of the millennium also marks the centenary of Canadian socialism, dated from 1901 (the first free-standing country-wide organization) or 1905 (the formation of the first electorally successful socialist party). By probing the logic and rhetoric of key texts from the Canadian socialist movement, we can discern four distinct formations--evolutionary science, revolutionary praxis, national State management, and revolutionary humanism and national liberation--in a history marked throughout by a hegemonic liberal order. These strategies are worth careful, sympathetic, and critical study as socialist movements regroup in the 21st century.